2015
DOI: 10.1155/2015/871947
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Carbapenem-ResistantKlebsiella pneumoniae: Progressive Spread and Four-Year Period of Observation in a Cardiac Surgery Division

Abstract: Frequent use of carbapenems has contributed to the increase to K. pneumoniae strains resistant to this class of antibiotics (CRKP), causing a problem in the clinical treatment of patients. This investigation reports the epidemiology, genetic diversity, and clinical implication of the resistance to drugs mediated by CRKP in our hospital. A total of 280 K. pneumoniae strains were collected; in particular 98/280 (35%) were CRKP. Sequencing analysis of CRKP isolated strains showed that 9/98 of MBL-producing strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
(25 reference statements)
1
11
1
2
Order By: Relevance
“…In our study, we found that CRKP had a low resistance rate to compound sulfamethoxazole (21.65%), which was similar to the findings in a previous report [ 26 ]. In vitro , Su et al [ 27 ] found that compound sulfamethoxazole combined with polymyxin could quickly kill CRKP isolates within 2 to 24 h. However, there was a lack of evidence-based medicine for clinical treatment of CRKP using compound sulfamethoxazole, and this finding needed to be confirmed by further clinical studies [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found that CRKP had a low resistance rate to compound sulfamethoxazole (21.65%), which was similar to the findings in a previous report [ 26 ]. In vitro , Su et al [ 27 ] found that compound sulfamethoxazole combined with polymyxin could quickly kill CRKP isolates within 2 to 24 h. However, there was a lack of evidence-based medicine for clinical treatment of CRKP using compound sulfamethoxazole, and this finding needed to be confirmed by further clinical studies [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…have the ability to acquire resistance genes by mutations and more commonly by transmissible plasmids. 27 Progressive spread and increasing incidence of carbapenem resistance among Klebsiella spp. has become a severe public health issue.…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella pneumoniae (K. pneumoniae) is one of the most important causes of infection especially among hospitalized patients [1]. Multi-drug resistant (MDR) K. pneumoniae isolates are becoming increasingly prevalent in the clinical and nosocomial environments and is raised as a major threat in treatment of nosocomial infections [2]. Different mechanisms and factors involved in the development and spread of antibiotic resistance in bacterial strains.…”
Section: Introductionmentioning
confidence: 99%